Comparative Study of the Undergraduate Nursing Curricula Among Nursing Schools of McMaster University of Canada, Hacettepe University of Turkey, and Tehran University of Iran - Fatemeh Keshmiri (Strides in Development of Medical Education, 2019)
Context Evaluation of different education systems or approaches can help improve educational quality. To implement a program successfully, it is essential to examine the curricula of leading countries from different aspects. The present study aimed at comparing the bachelor of science in nursing (BSN) programs at nursing schools of McMaster in Canada, Hacettepe of Turkey, and Tehran (Iran). Evidence Acquisition The current descriptive-comparative study was performed in 2016 using the Brody method; the BSN programs were compared among Nursing School of Tehran University of Medical Sciences in Iran, Faculty of Nursing at Hacettepe University of Turkey, and McMaster School of Nursing in Canada. Results In the BSN program curricula of Tehran and Hacettepe universities, no correlation was found between contents and educational goals (theoretical and clinical), while a significant conformity was found between the theoretical and clinical goals of courses offered in the BSN curriculum of McMaster University. The ability to transfer leadership, management, communication, critical thinking, and clinical decision-making skills were formally ignored in the BSN curriculum of University of Tehran, while the mentors act just as a role model. There were programs and workshops for practicing critical thinking in Hecettepe University, while the evidence-based nursing and research in nursing were stressed in educational goals; the points disregarded in the curriculum of the BSN program of the University of Tehran. Conclusions It seems that the School of Nursing and Midwifery of Tehran University of Medical Sciences should reconsider educational goals and content and pay more attention to issues such as problem solving, critical thinking, clinical judgment, and efficient leadership skills, as well as creativity and innovation.